Snakebite Affecting both Human and Animal Dates Back 1870: A Historical Perspective - Rashid, Rumana; Fairouz, Fariha; Sayeed, Abdullah Abu; Amin, Md Robed; Faiz, MA (Bangladesh Journal of Medicine, 2021)
Abstract not available Bangladesh J Medicine July 2022; 33(1) : 126-127